Perancangan sistem inventory barang gudang berbasis website - Diah Angraina Fitri; Julia Sofia (Universitas Muhammadiyah Riau, 2023)
A warehouse is a room used to store various types of goods. All types of buildings can have warehouses, for example warehouses in factory buildings, shops and even residential buildings. It is used to store various types of goods, warehouses usually have the ability to store dust. Therefore, the location of the warehouse must be considered so as not to interfere with other activities in the building. But in this day and age, a business still uses manual registration or bookkeeping. Manual record keeping is very difficult between warehouse workers and office administrators. This research builds an online reservation application for warehouse accounting. This system is built with the PHP programming language and MySQL database supported by a responsive web design. The resulting system meets the needs of inventory accounting in the warehouse. This system aims to facilitate registration and administration related to the registration of goods in the warehouse.